Efficiency of Nitrogen and Phosphorus Fertilizer With Vesicular Arbuscular Mycorrhiza (VAM) Applicatio Yield of Situbagendit Rice Variety On Rainfed Lowland Rice - Achmad Fatchul Aziez; Setie Harieni; Daryanti; Dika Saputra (Faculty of Agriculture, Merdeka University Surabaya, 2020)
The area of rainfed lowland rice in Indonesia was 3,292,578 ha or 24% of the total area of rice, but the used is still very small, so that opportunities are still open for the development of rice plants. The main constraints on rainfed lowland are drought stress and inefficient use of nitrogen (N) and phosphorus (P) nutrients. The purpose of this study was to determine the effect of mycorrhizal fungi on the efficient use of nitrogen and phosphorus in rice planted in rainfed lowland. This research was conducted in rainfed lowland in April to July 2019 in the village of Demangan, Sambi, Boyolali, Central Java. The research method was a randomized completely block design. Factor 1: Doses of nitrogen fertilizer (N) 0; 45; 90; 135 kg/ha. Factor 2: phosphorus dose (P) 0; 25; 50; 75 kg/ha. Observations included the number of total tillers, number of productive tillers, panicle number, panicle length, 1000 grain weight, and grain weight per plot. Data Analysis was analysis of variance. If there was a difference between treatments then it was tested further by using Duncan's New Multiple Range Test at 5% level. To know the relationship of direct and indirect influence, regression and correlation analysis were done. Data were analyzed by computer using SAS for window 9.0 programs. The results showed that the application of VAM could save the use of nitrogen fertilizer and eliminate the use of phosphorus fertilizer.